Perceiving machines : Leibniz's teleological approach to perception - Vargas, Evelyn (2011)
Evelyn Vargas focuses on the epistemological problems involved in Leibniz's successive definitions of perception in the context of the development of a theory of the actions and the passions of created substances. Although his first characterization of perceptual experience involves "cogitation" or thought that is related to an object as its requisite his newly developed science of dynamics makes it possible to introduce a teleological approach to perception by which sentience can be extended to animals or even living machines more generally. Insofar as perception can be regarded as an organic function it can be treated within the dynamical framework of the exercise of forces. Despite the advantages of this innovating view of perceptual representation without thought, the scope of such an account beyond the limits of empirical disciplines related to medical practice can be put into question once pre-established harmony enters the picture. If the causal vocabulary ordinarily used in our statements concerning the objects of perception is properly understood, the epistemic connection between sensory experience and external objects has to be reconsidered. However, Vargas argues, Leibniz's teleological conception of sentience can provide a univocal description of both human and animal perception while preserving its informative role.